Inferring a shape grammar: translating designer's knowledge - Eloy, S. (2015)
This article focuses on a shape grammar that was developed to enable the adaptation of existing houses – “rabo-de-bacalhau” housing style - to new requirements and most particular on the process of inference of the grammar. Along the article we describe the process undertaken to develop the grammar and what the achievements of the transformation grammar are regarding the possibilities of a mass customization of dwelling’s rehabilitation work. The goal of this article is to describe and discuss how the designer’s knowledge was encoded into shape rules. The process used to extract the architect’s knowledge and to incorporate it into the transformation grammar enable to abstract the designer’s actions and to define a sequence of actions that can define a possible strategy of design. The proposed design methodology generates dwelling layouts that are legal since they follow the grammar language and adequate since they meet the a priori user and design requirements.